Amyloid‐β Dysregulates Oligodendroglial Lineage Cell Dynamics and Myelination via PKC in the Zebrafish Spinal Cord - Uxue Balantzategi; Adhara Gaminde‐Blasco; Christina A. Kearns; Laura Bayón‐Cordero; Marı́a Victoria Sánchez-Gómez; José L. Zugaza; Bruce Appel; Elena Alberdi (2025)
ABSTRACT Soluble forms of amyloid‐β (Aβ) peptide have been proposed as candidates to induce oligodendrocyte (OL) and myelin dysfunctions in the early stages of Alzheimer's disease (AD) pathology. Nevertheless, little is known about how Aβ affects OL differentiation and myelination in vivo, and the underlying molecular mechanisms. In this study, we explored the effects of a brain intraventricular injection of Aβ on OLs and myelin in the developing spinal cord of zebrafish larvae. Using quantitative fluorescent in situ RNA hybridization assays, we demonstrated that Aβ altered myrf and mbp mRNA levels and the regional distribution of mbp during larval development, suggesting an early differentiation of OLs. Through live imaging of Tg ( myrf:mScarlet ) and Tg ( mbpa:tagRFP ) zebrafish lines, both crossed with Tg ( olig2:EGFP ), we found that Aβ increased the number of myrf + and mbp + OLs in the dorsal spinal cord at 72 hpf and 5 dpf, respectively, without affecting total cell numbers. Furthermore, Aβ also increased the number of Sox10 + cells, myelin sheaths per OL, and the number of myelinated axons in the dorsal spinal cord at 8 dpf compared to vehicle‐injected control animals. Interestingly, the treatment of Aβ‐injected zebrafish with the pan‐PKC inhibitor Gö6983 restored the aforementioned alterations in OLs and myelin to control levels. Altogether, not only do we demonstrate that Aβ induces a precocious oligodendroglial differentiation leading to dysregulated myelination, but we also identified PKC as a key player in Aβ‐induced pathology.